2019
DOI: 10.1111/jcpt.13013
|View full text |Cite
|
Sign up to set email alerts
|

The impact of evidence from clinical trials on counselling for over‐the‐counter drugs: A national survey of pharmaceutical staff in German pharmacies

Abstract: What is known and objective: Evidence from clinical trials should form the foundation of healthcare advice. Comparatively little has been investigated about the implementation of evidence in over-the-counter (OTC) counselling in community pharmacies. The objective of this study was to explore the current impact of clinical trials on OTC counselling from the perspective of pharmaceutical staff. Methods: Pharmaceutical staff in German community pharmacies were invited to participate in a nationwide cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…A precise number of individuals who received the survey is therefore not known. The study's data set was collected in a two-part online survey together with a study, which evaluated the use of clinical study data in self-medication consultations [41].…”
Section: Study Part A: Self-reportmentioning
confidence: 99%
“…A precise number of individuals who received the survey is therefore not known. The study's data set was collected in a two-part online survey together with a study, which evaluated the use of clinical study data in self-medication consultations [41].…”
Section: Study Part A: Self-reportmentioning
confidence: 99%
“…To support implementation of evidence-based principles in the community pharmacy in Germany, a perspective paper was developed in a bottom-up manner by more than 4000 pharmacists [5]. This is particularly important, because pharmacists have not yet consistently implemented an evidence-based approach to their counseling practice [6][7][8][9][10][11][12]. They face difficulties in incorporating research findings into practice [6].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important, because pharmacists have not yet consistently implemented an evidence-based approach to their counseling practice [6][7][8][9][10][11][12]. They face difficulties in incorporating research findings into practice [6]. Despite that pharmacists are obliged and encouraged to pursue continuing education [13,14], several studies have demonstrated a lack of pharmacists' knowledge and skills as major obstacles to the practice of evidence-based care [7,8,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations